PELATIHAN PENGELASAN 1G, GUNA MENINGKATKAN PENDAPATAN DAN KEMAMPUAN ANDIKPAS PASCA BEBAS DARI LEMBAGA PEMASYARAKATAN KHUSUS ANAK TOMOHON - Moh Fikri Pomalingo (UPPM Politeknik Gorontalo, 2021)
In juvenile criminal justice in Indonesia, the government made a special institution for taking with dealing with this matter. These institutions are known as LPKA and LPAS. The results of the team discussion with the head of LPKA Tomohon, information was obtained that, there was still a lack of guidance related to improving children's abilities. One of these improvements is related to welding training. Beside, the LPKA has provided room facility and plans to build a welding workshop, but the cost is constrained, so it has not been realized. The Unima service team through the Community Partnership Program has realized the welding training. The methods applied include making welding workshops, giving theories related to welding, using machines, measuring, cutting materials, and painting, as well as giving practice and making assignments. Theoretical activities were carried out for 6 days and practical activities for 21 days. The types of welding being trained are 1G and 2G. The results obtained, all the participants, totaling 20 people, were able to carry out the training well. This is indicated by the presentation results which are above 90%. This training, too, provides good product results. This activity was carried out during the COVID-19 pandemic, but all participants and teams carried out activities by adhering to strict health protocols.